Utilisation of Directors' Remuneration in Tax Planning - Abdul Wahab, Nor Shaipah; Che Pak, Nur Azliani Haniza (Universiti Utara Malaysia Press, 2011)
Companies involve in tax planning due to its primary benefit of increase after-tax return. However, this activity has been an ongoing discussion as it impairs provision of public goods which indirectly causes social issues. Companies, in conducting tax planning, make use of several techniques to effectively minimise the tax burden, for example, profit sharing, income shifting and change of characteristics of income. Directors' remuneration is also identified as a tax-reduction strategy. While increasing the wealth of the directors, higher directors' remuneration expense reduces company taxable income and in turn raises company tax savings. This provides indications about the missing link between directors' performance and pay. In fact, in Malaysia, this issue has been long debated by the public including academics. Despite this highlight, little attention has been given to the relationship between tax planning and directors' remuneration. Therefore, this paper reports the results of this study's focus of attention on whether tax planning activity is significantly related to directors' remuneration expenses of non-financial Malaysian public-listed companies. The sample period of the study is from 2007 to 2009. The panel dataset is drawn from Data stream and hand-collected tax data from company annual reports. The results derived from the multivariate analyses highlight the extent of the relationship between tax planning and directors' remuneration and thus enlighten the knowledge on the utilisation of directors' remuneration as a strategy in tax planning. The results also highlight the policy and reporting implications to the authority.